2006
DOI: 10.1128/jcm.01488-06
|View full text |Cite
|
Sign up to set email alerts
|

Misidentification of a Mucoid Strain of Salmonella enterica Serotype Choleraesuis as Hafnia alvei by the Vitek GNI+ Card System

Abstract: Nontyphoidal salmonellae are among the most common causes of bacterial gastroenteritis worldwide. They are also notable causes of extraintestinal infections, including bacteremia and vascular infections. Salmonella enterica serotype Choleraesuis is typically associated with invasive infections. We report a patient who had an infected intra-abdominal aortic aneurysm due to an unusually mucoid strain of Salmonella enterica serotype Choleraesuis. The isolate was erroneously identified as Hafnia alvei by the Vitek… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 14 publications
0
8
1
Order By: Relevance
“…[9]. In the present study, PCR assays using two combinations of primers were designed for the detection of E.…”
Section: Introductionmentioning
confidence: 99%
“…[9]. In the present study, PCR assays using two combinations of primers were designed for the detection of E.…”
Section: Introductionmentioning
confidence: 99%
“…Most of this research on CA was carried out with E. coli strains (5), such as different laboratory K-12 strains, including MC4100, MG1655, and W3310 (6,8,17,30,31,(37)(38)(39)(40), K1 (41), K5 (41), K92 (42), extraintestinal isolate O4/K54/H5 (35,43), different O8 and O9 pathovars (44), enterohemorrhagic E. coli O157:H7 (18,26,27,36,37,45), and uropathogenic E. coli (33). Although it was reported that CA in Salmonella is not important for biofilm formation in vitro (46), some reports indicated that CA in Salmonella may play a role in vivo (4,47,48). The divergence of CA gene clusters between Salmonella and E. coli is slightly higher than the average for other genes of the two species (4).…”
mentioning
confidence: 99%
“…Mucoid Salmonella strains were not lysed by P22, indicating the inaccessibility to the P22 receptor LPS O antigen (49). A mucoid variant of Salmonella has been isolated from a clinical specimen, which indicated that CA overexpression in vivo may help Salmonella escape antibiotic treatment (48). Although the physiological stimuli in vivo that induce CA synthesis are not fully understood (50), mutation of wcaM, one of the CA synthesis genes in Salmonella, resulted in reduced biofilm formation on HEp-2 cells and on chicken intestinal tissue at 37°C in vitro (47), which indicated that the CA can be produced at 37°C when bacteria are exposed to eukaryotic cells.…”
mentioning
confidence: 99%
“…The commercial systems, often used by clinical and food laboratories to identify gram‐negative rods, identified E. albertii isolates as Hafnia, E. coli, Salmonella , or Yersinia ruckeri (Abbott et al , 2003). Automated bacterial identification systems have limitations as documented in a recent report where a clinical mucoid strain of Salmonella enterica serovar choleraesuis was identified as H. alvei (Wang et al , 2006). Since E. albertii has just been described, the lack of biochemical identification of these strains may have jeopardized the scope of research involving its occurrence and association with food‐borne illness.…”
Section: Introductionmentioning
confidence: 99%